Challenges of Small and Medium Enterprise towards Progress - Leslie Ann Gamundoy; Remedios Bucal; Flordeliza Em (Philippine Association of Institutions for Research, Inc., 2020)
The major concern of this study is to identify the challenges of small and medium enterprises towards progress in Pulo in the City of Cabuyao, Laguna, the Philippines as assessed by the business owner- respondents. By understanding their challenges, it is expected to improve the competitiveness of SMEs, and that eventually, they will grow and expand their businesses. When it comes to the nature of the business, the service type is the most commonly used by the medium enterprise business-owners with the least capitalization of 11,000 and up and with a capacity of 11 years of business operations. They all agreed that they encounter some difficulties in availing of funds because of lots of requirements in loan applications for business. They are also amenable to growing stiff competition that arises among the unregistered enterprises because of much cheaper offered products to the market. In this case, some SMEs have failed to compete with the micro-businesses. They all disagree on the perception that the focus on giving support is intended only for micro-enterprises, same as the LGU for the insufficient fund to support in promoting more the SME sector.